ЕНГИЛ САНОАТ ЙЎНАЛИШДАГИ ТАЛАБАЛАРДА ИНТЕРФАОЛ МЕТОДЛАРДАН ФОЙДАЛАНИБ НАҚШБАНДИЯ ТАЪЛИМОТИДАГИ ҲАЛОЛЛИК ТУШУНЧАЛАРНИНГ СИНГДИРИШ - Убайдова, В.Э. (SCIENCE and SOCIETY, 2022)
The article reveals the essence and significance of the principle of honesty in the teachings of Naqshbandi, founded by Muhammad ibn Muhammad al-Bukhari (1318-1389), known as Bahauddin Naqshband, in teaching students of light industry in higher educational institutions. Methods and innovative tools for applying the principle of honesty in the teachings of Naqshbandi at the present time in the training of light industry specialists are revealed, and the importance of eliminating corruption is revealed in the system of today’s education and raising honest (halal) students.